The Palgrave Handbook of Social Theory in Health, Illness and Medicine - Collyer, F. (Palgrave Macmillan, 2020)
This wide-reaching handbook offers a new perspective on the sociology of health, illness and medicine by stressing the importance of social theory. Examining a range of classic and contemporary female and male theorists from across the globe, it explores various issues including chronic illness, counselling and the rising problems of obesity.